Study of Patterns of Lip Prints and Sex Determination in a Suburban Region of Dakshina Kannada District. A 2 Year Prospective Study - Fouzia Hameed; Vina Vaswani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cheiloscopy (quiloscopy) is a method of identification of a person based on characteristic arrangement of lines appearing on the red part of lips. Lip prints are unique to an individual, and persist in their characteristics over a period of years. They are like fingerprints reliable method for identification. The aim of the study was to find out various patterns of lip prints and the commonest pattern observed in both males and females. Materials and method: The study was carried out on 200 individuals residing in suburban area in Dakshina Kannada District, of ages ranging from 12-60yrs of both sexes after taking consent. The present study was carried out from 2013 to 2015.The materials used were dark colour lipstick, bond paper, cello tape. Results: The common pattern of lip print observed was Type I in the entire study population in both males and females. In Dakshina Kannada however it was not statistically proved significant. There was no significance between patterns and gender.